Experimental Investigation of Large Time–Bandwidth Product Photonic Hilbert Transformer Based on Compact Bragg Grating - B. Liu; C. Sima; W. Yang; C. Cai; D. Liu; Y. Yu; J. Gates; M. Zervas; P. Smith (IEEE Photonics Journal)
We propose and experimentally demonstrate an integrated photonic Hilbert transformer (PHT) with substantial time bandwidth product (TBP). Due to the current substrate material and fabrication technique, PHT devices find it challenging to achieve ultrawide operative bandwidth while maintaining the minimum bandwidth level presented as the narrow central notch in frequency response. This implies that the TBP value is restricted. Here, we investigate the synthesized refractive index profile in compact Bragg grating design for theoretical simulation and the linearity-enhanced direct UV grating writing fabrication for experimental implementation. The fabricated device could process microwave photonic signals as Hilbert transformation between 50 GHz and 3 THz, with the TBP above 60, which is the largest experimental data to the best of our knowledge. This technique allows the PHT with improved spectral performance to be suitable for analog all-optical signal processing.